Pengembangan E-LKPD Berbasis PBL Terintegrasi AI pada Materi Klasifikasi Makhluk Hidup untuk Meningkatkan HOTS dan KPS - Eunike Manurung; Khairiza Lubis; Melva Silitonga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop and evaluate the feasibility and effectiveness of an Electronic Student Worksheet (E-LKPD) based on Problem-Based Learning (PBL) integrated with Artificial Intelligence (AI) on the topic of classification of living organisms, to enhance students’ Higher Order Thinking Skills (HOTS) and Science Process Skills (SPS). The research employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate). Effectiveness testing was conducted through a quasi-experimental design using a pretest-posttest control group. Data were analyzed using independent sample t-test and N-Gain analysis. The validation results indicated that the E-LKPD was in the “highly feasible” category. The t-test results for the pretest showed no significant difference between the experimental and control groups (t = 0.031; p = 0.975), while the posttest results revealed a significant difference (t = 7.403; p = 0.000). The N-Gain scores for HOTS and SPS were 0.61 and 0.68, respectively, both categorized as moderate and effective. It is concluded that the PBL-based E-LKPD integrated with AI is feasible and effective for improving students’ HOTS and SPS in biology learning. Keywords: AI, E-LKPD, HOTS, SPS, Problem Based Learning